1998
DOI: 10.5070/v418110164
|View full text |Cite
|
Sign up to set email alerts
|

Management of conflicts between urban coyotes and humans in Southern California

Abstract: An apparent increase in coyote-human conflicts, notably attacks on humans, demonstrates that such incidents are not rare in California. The authors discuss coyote attacks on 53 humans, resulting in 21 instances of human injury, over the last decade. These illustrate repeated, predictable pre-attack coyote behavior patterns. Specific changes in human environments and in human behavior that have contributed to coyote attacks are discussed. Case histories of attacks reveal contributing factors and suggest appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 12 publications
(12 reference statements)
1
53
0
Order By: Relevance
“…The word "attack" is used by the public, popular press, and wildlife professionals to include a wide variety of interactions between people and coyotes, including incidents such as a close-range coyote sighting in a residential neighborhood or the attack of a domestic pet in the presence of its owner (Fox, 2006). Previous reviews of coyote attacks have used broad definitions of the word "attack" to include incidents in which victims were either not injured by a coyote (e.g., stalking) or injured themselves while trying to rescue a pet from a coyote (sensu Baker & Timm, 1998;Timm et al, 2004). We chose to use a relatively conservative definition of a coyote attack for the following analyses.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The word "attack" is used by the public, popular press, and wildlife professionals to include a wide variety of interactions between people and coyotes, including incidents such as a close-range coyote sighting in a residential neighborhood or the attack of a domestic pet in the presence of its owner (Fox, 2006). Previous reviews of coyote attacks have used broad definitions of the word "attack" to include incidents in which victims were either not injured by a coyote (e.g., stalking) or injured themselves while trying to rescue a pet from a coyote (sensu Baker & Timm, 1998;Timm et al, 2004). We chose to use a relatively conservative definition of a coyote attack for the following analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Previous reviews of coyote attacks have not identified attacks by rabid coyotes (Carbyn, 1989;Baker & Timm, 1998;Timm et al, 2004). We recorded 10 cases of confirmed rabid coyote attacks, which resulted in 15 bite victims.…”
Section: Role Of Rabies In Attacksmentioning
confidence: 96%
See 3 more Smart Citations